2016
DOI: 10.2118/166306-pa
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Compositional Modeling in Unconventional Shale Reservoirs

Abstract: Understanding the mechanism of multicomponent mass transport in the nanopores of unconventional reservoirs, such as Eagle Ford, Niobrara, Woodford, and Bakken, is of great interest because it influences long-term economic development of such reservoirs. Thus, we began to examine the phase behavior and flow characteristics of multicomponent flow in primary production in nanoporous reservoirs. Besides primary recovery, our long-term objectives included enhanced oil production from such reservoirs. The first step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…55 To better understand liquid-rich shales, hydrocarbon mixtures with heavier hydrocarbons should be considered. 27,65,69 To this end, the methane/n-butane (CH 4 /n-C 4 H 10 ) mixture would be an ideal choice, as it can represent both the bubble-point and gas-condensate dew-point fluid systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…55 To better understand liquid-rich shales, hydrocarbon mixtures with heavier hydrocarbons should be considered. 27,65,69 To this end, the methane/n-butane (CH 4 /n-C 4 H 10 ) mixture would be an ideal choice, as it can represent both the bubble-point and gas-condensate dew-point fluid systems.…”
Section: Introductionmentioning
confidence: 99%
“…The critical pressure of the confined fluid decreases and the supercritical region expands to a lower pressure than that of the corresponding bulk system. Recently, it was reported that the bubble point in nanoporous media is almost the same as the dew-point pressure, both of which are lower than the dew-point line of the corresponding bulk mixture . There are three commonly used methods to model the phase behavior in shale nanopores: (1) consider the influence of the capillary pressure; ,,,,, (2) modify the critical temperature and pressure in the equation of state (EoS) models; , and (3) modify the equation of state. Besides, researchers have considered the adsorption effect, , but details differ: Dong et al emphasized the importance to subtract the thickness of adsorption film from the pore diameter, the equation of state was modified to mimic the adsorption effect in other groups, and Sandoval et al considered the adsorption effect with the multicomponent Langmuir model, of which the parameters were determined by the multicomponent potential theory of adsorption . However, these methods remain to be testified and improved .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shale formations account for about 75% of drilled formations worldwide (Osisanya and Chenevert, 1994). The shale formation has a large amount of micropores (Alharthy et al, 2013(Alharthy et al, , 2016). On the one hand, the invasion of drilling fluids into micropores during the drilling process causes hydration and expansion of clay minerals (Luo et al, 2017;Huang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…In the natural environment, multicomponent systems with highly curved interfaces can be found from 4 km below the Earth’s crust in hydrocarbon reservoirs to up to 15 km above the surface in the troposphere. , In the subsurface, porous structures can have pore throat diameters in the nanometer range. These nanopores influence phase equilibrium, and if their effect is unaccounted for, predictions for unconventional hydrocarbon recovery operations may be inaccurate. Phase diagrams are vital tools in recovering oil and natural gas from shale formations, and the effect of nanoscale curvature on phase diagrams has been calculated for specific compositions of hydrocarbons as a function of temperature and pressure. ,, In the atmosphere, clouds can form when water condenses on highly curved nuclei with diameters in the nanometer range. , The number, size, and composition of these nuclei determine the number and size of water droplets, which dictate the size and lifetime of clouds . Thus, nanoscale processes can have a significant role in macroscopic properties and phenomena.…”
Section: Introductionmentioning
confidence: 99%